Compressive Strength and Thermal Resistance of Geopolymer Mortar Containing Fly Ash and Red Mud Blend - Ong, Melody Huei Qie; Ismail, Amalina Hanani; Kusbiantoro, Andri (Progress in Engineering Application and Technology, 2025)
Cement is a widely used material in the construction industry. However, its production significantly contributes to carbon dioxide (CO2) emissions and other harmful gases due to high-temperature calcination process involved in ordinary Portland cement (OPC) production. To address this environmental issue, researchers have shifted their focus toward alternative binder materials such as geopolymer. Geopolymer is synthesized through a polycondensation of aluminosilicate materials activated by an alkaline activator, utilizing industrial by-products rich in silica and alumina. This study investigates the effects of incorporating red mud in varying proportions (0%, 2%, 4%, 6%, 8% and 10%) as partial source material replacement in fly ash-based geopolymer mortar. While fly ash, with its high silica and alumina content, is a well-established geopolymer precursor, the potential of red mud remains underexplored despite its comparable chemical composition. The mortar was tested for density, compressive strength and thermal conductivity at curing intervals of 7 and 28 days. To evaluate long-term strength development, additional compressive strength tests were conducted at 56 days. Based on this study, the results showed that 6% red mud achieved the highest compressive strength of 47.04 Mpa at 7 days surpassing the control mix. Thermal conductivity decreased with increasing red mud content indicating improved thermal resistance. However, proportions above 6% reduced compressive strength due to increased porosity. This study demonstrates that the best proportion, 6% RM for balancing compressive strength and thermal resistance. These findings highlight red mud’s feasibility as an alternative source material in fly ash-based geopolymer mortar contributing to sustainable construction practices and the effective utilization of industrial waste.